Suitability of Thrombolysis for Patients With Acute Ischemic Stroke Complicated With Trousseau Syndrome - Chen, Yujie; Zhang, Chundi; Wang, Xin; Han, Long; Zhu, Shiguang; Liu, Yan; Wang, Rui; Geng, Ziyang; Ma, Chenchen; Dong, Ruiguo (Frontiers in Neuroscience, 2020)
Abstract Intravenous thrombolysis (IVT) improves functional outcome after acute ischemic stroke (AIS) and is the standard first-line treatment; however, it is associated with many complications, including cerebral hemorrhage. Cancer patients are susceptible to thrombotic events—collectively referred to as Trousseau syndrome (TS)—owing to their hypercoagulable state. Here we describe the case of a 55-year-old male with a history of hypertension for over 10 years who underwent surgery for removal of a cancer of lower esophagus, with no subsequent treatment. Three months later, he was admitted to the emergency department of our hospital with sudden dizziness and incoherent speech. Brain computed tomography revealed multiple cerebral infarctions. The patient was treated by IVT with tissue plasminogen activator (rtPA) after the onset of symptoms, which improved by the end of the treatment. However, a few months later he experienced a recurrence of cerebral infarction and hemorrhage, which has rarely been reported. The clinical course of this case suggests that the suitability of thrombolysis with rtPA in the acute phase of cerebral infarction complicated with TS should be carefully considered.